1999
DOI: 10.1289/ehp.99107721
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of pesticides and polycyclic aromatic hydrocarbons in house dust as a function of particle size.

Abstract: House dust is a repository for environmental pollutants that may accumulate indoors from both internal and external sources over long periods of time. Dust and tracked-in soil accumulate most efficiently in carpets, and the pollutants associated with dust and soil may present an exposure risk to infants and toddlers, who spend significant portions of their time in contact with or in close proximity to the floor and who engage in frequent mouthing activities. The availability of carpet dust for exposure by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(55 citation statements)
references
References 12 publications
3
50
2
Order By: Relevance
“…In general, carpet dust PAH concentrations measured in our study were lower than previously reported levels in Durham, NC, USA [44, 45] and Ottawa, Canada [46]. However, measured concentrations in this multicenter study were considerably higher than those measured in the California Childhood Leukemia Study (CCLS), a recent case–control study conducted in the San Francisco Bay area and the Central Valley, USA [47].…”
Section: Discussioncontrasting
confidence: 73%
“…In general, carpet dust PAH concentrations measured in our study were lower than previously reported levels in Durham, NC, USA [44, 45] and Ottawa, Canada [46]. However, measured concentrations in this multicenter study were considerably higher than those measured in the California Childhood Leukemia Study (CCLS), a recent case–control study conducted in the San Francisco Bay area and the Central Valley, USA [47].…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have shown that carpets can harbor large amounts of lead, house dust mite (HDM) allergens, PAHs, and other chemical substances. 25 Without proper cleaning, these contaminants are accessible and potentially harmful to young children. 610 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, exposure to house dust is a significant pathway for the children’s exposure to pesticides [9,11]. Studies also indicate that more pesticides and higher pesticide concentrations are found in household dust as compared to air, soil, and food [24,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Carbamates and pyrethroids are semi- or less volatile pesticides that tend to settle in house dust [24]. We expect that these are the pesticides that will accumulate in the dust samples because spray pesticides and slow-burning mosquito coils which contain these pesticides are regularly used in the homes of the subjects [28].…”
Section: Discussionmentioning
confidence: 99%